Hot Topics in Endocrinology and Metabolism 2021
DOI: 10.5772/intechopen.96309
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of Human Exposure to Bisphenol A and Its Novel Implications on Renal, Cardiovascular and Hypertensive Diseases

Abstract: Bisphenol A (BPA), an endocrine disruptor involved in synthesizing numerous types of plastics, is detected in almost the entire population’s urine. The present work aims to estimate daily exposure to BPA by systematically reviewing all articles with original data related to urinary BPA concentration. This approach is based on human pharmacokinetic models, which have shown that 100% of BPA (free and metabolized form) is eliminated only in a few hours through urine. Several extensive population studies and exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 118 publications
2
3
0
Order By: Relevance
“…The proportion of men and women was practically the same. The urinary BPA concentration was relatively low and consistent with the data observed in the general population [46]. Men had significantly higher BPA values per mL of urine but significantly lower BPA corrected for creatinine.…”
Section: Nhanes 03-16 Cohortsupporting
confidence: 87%
“…The proportion of men and women was practically the same. The urinary BPA concentration was relatively low and consistent with the data observed in the general population [46]. Men had significantly higher BPA values per mL of urine but significantly lower BPA corrected for creatinine.…”
Section: Nhanes 03-16 Cohortsupporting
confidence: 87%
“…Today there is still controversy about the degree of exposure to BPA and the doses considered safe. In a recent analysis of our group, it was determined that the mean urinary concentration of BPA in the general population is close to 10 nM, which may be related to ingested concentrations close to the doses used in our study [73]. The doses used in the present work, 100 nM and 5 µM, have been detected in certain groups with high exposure, such as workers in the plastic industry [74][75][76][77].…”
Section: Discussionsupporting
confidence: 64%
“…Several studies have suggested that the degree of BPA toxicity to human and animal health depends on the dose, duration of exposure, age of the exposed individual and frequency of exposure (3,31,32). Liver and kidney are the organs with the highest bioaccumulation of BPA (33); therefore, these organs should be checked for BPA accumulation. Several studies have reported that BPA interacts with nuclear receptors, including oestrogen receptors, PPARs, retinoid and thyroid receptors (34).…”
Section: Discussionmentioning
confidence: 99%